Immunogenicity and safety of fractional doses of yellow fever vaccines: a randomised, double-blind, non-inferiority trial. Issue 10269 (9th January 2021) - Juan-Giner, Aitana; Kimathi, Derick; Grantz, Kyra H; Hamaluba, Mainga; Kazooba, Patrick; Njuguna, Patricia; Fall, Gamou; Dia, Moussa; Bob, Ndeye S; Monath, Thomas P; Barrett, Alan D; Hombach, Joachim; et al.
Summary: Background: Stocks of yellow fever vaccine are insufficient to cover exceptional demands for outbreak response. Fractional dosing has shown efficacy, but evidence is limited to the 17DD substrain vaccine. We assessed the immunogenicity and safety of one-fifth fractional dose compared with standard dose of four WHO-prequalified yellow fever vaccines produced from three substrains. Methods: We did this randomised, double-blind, non-inferiority trial at research centres in Mbarara, Uganda, and Kilifi, Kenya. Eligible participants were aged 18–59 years, had no contraindications for vaccination, were not pregnant or lactating, had no history of yellow fever vaccination or infection, and did not require yellow fever vaccination for travel. Eligible participants were recruited from communities and randomly assigned to one of eight groups, corresponding to the four vaccines at standard or fractional dose. The vaccine was administered subcutaneously by nurses who were not masked to treatment, but participants and other study personnel were masked to vaccine allocation. The primary outcome was proportion of participants with seroconversion 28 days after vaccination. Seroconversion was defined as post-vaccination neutralising antibody titres at least 4 times pre-vaccination measurement measured by 50% plaque reduction neutralisation test (PRNT50 ). We defined non-inferiority as less than 10% decrease in seroconversion in fractional compared with standard dose groups 28 days after vaccination. The primary outcome was measured in the per-protocol population, and safety analyses included all vaccinated participants. This trial is registered with ClinicalTrials.gov, NCT02991495 . Findings: Between Nov 6, 2017, and Feb 21, 2018, 1029 participants were assessed for inclusion. 69 people were ineligible, and 960 participants were enrolled and randomly assigned to vaccine manufacturer and dose (120 to Bio-Manguinhos-Fiocruz standard dose, 120 to Bio-Manguinhos-Fiocruz fractional dose, 120 to Chumakov Institute of Poliomyelitis and Viral Encephalitides standard dose, 120 to Chumakov Institute of Poliomyelitis and Viral Encephalitides fractional dose, 120 to Institut Pasteur Dakar standard dose, 120 to Institut Pasteur Dakar fractional dose, 120 to Sanofi Pasteur standard dose, and 120 to Sanofi Pasteur fractional dose). 49 participants had detectable PRNT50 at baseline and 11 had missing PRNT50 results at baseline or 28 days. 900 were included in the per-protocol analysis. 959 participants were included in the safety analysis. The absolute difference in seroconversion between fractional and standard doses by vaccine was 1·71% (95% CI −2·60 to 5·28) for Bio-Manguinhos-Fiocruz, −0·90% (–4·24 to 3·13) for Chumakov Institute of Poliomyelitis and Viral Encephalitides, 1·82% (–2·75 to 5·39) for Institut Pasteur Dakar, and 0·0% (–3·32 to 3·29) for Sanofi Pasteur. Fractional doses from all four vaccines met the non-inferiority criterion. The most common treatment-related adverse events were headache (22·2%), fatigue (13·7%), myalgia (13·3%) and self-reported fever (9·0%). There were no study-vaccine related serious adverse events. Interpretation: Fractional doses of all WHO-prequalified yellow fever vaccines were non-inferior to the standard dose in inducing seroconversion 28 days after vaccination, with no major safety concerns. These results support the use of fractional dosage in the general adult population for outbreak response in situations of vaccine shortage. Funding: The study was funded by Médecins Sans Frontières Foundation, Wellcome Trust (grant no. 092654), and the UK Department for International Development. Vaccines were donated in kind.